Computational Thinking in pre-university Blended Learning classrooms. (March 2018) - Basogain, Xabier; Olabe, Miguel Ángel; Olabe, Juan Carlos; Rico, Mauricio Javier
Abstract: This article describes the implementation of various core elements of Computational Thinking (CT) in the classrooms of schools of Latin America and USA in two specific courses: PC-01 and ECE130. These courses were designed for students of primary and secondary education, as well as for students of high school as part of a dual enrollment program with a local university. Both courses introduce the core concepts and processes of CT aided by the visual programming environments Scratch and Alice. The courses are facilitated by the classroom teacher with the support of a learning platform. This platform is configured to provide innovative pedagogical strategies based on emerging educational technologies. This article describes the concepts integrated under the term CT, and discusses the benefits of learning environments used to incorporate CT in the classroom. It describes as well the syllabi and assessments of both courses, and analyzes their impact of these courses on the educational institutions, the teachers and the students. Highlights: Computational Thinking trough object-based programming. Human Cognitive Primitives: in search of new computational tools. Blended Learning: added value for teachers and students. Student Peer Review: new roles and responsibilities for students. Mastery Learning through student portfolios and peer review.